Pengaruh Pengungkapan Corporate Social Responsibility terhadap Kinerja Keuangan dan Harga Saham pada Sektor Properti di Bursa Efek Indonesia - Hidayansyah, Putri Fika; Hubeis, Musa; Irwanto, Abdul Kohar (Jurnal Manajemen dan Organisasi, 2015)
The company operational activities are performed with the purpose to maximize shareholder values; however, the company's activities have impacts on environment, social, economiy and community. In order to comply with the government regulation, companies must conduct Corporate Social Responsibility (CSR), because investors are more interested in companies which have a good image in the community. This leads to make consumer loyalty higher and subsequently increases the company's profitability and company's stock values. The purpose of this study was to analyze the influence of CSR disclosure on Corporate Financial Performance (CFP) and stock prices. This study used 20 samples of property companies in the Indonesia’s Stock Exchange selected by purposive sampling. Data were processed and analyzed using Structural Equation Modeling (SEM) with software smartPLS. This research shows that valid indicators measure CSR at property sector include environment, human rights and society. A valid indicator measuring financial performance construct is only Market Value Added (MVA) and stock return is the valid indicator to measure stock price construct. The hypothesis test shows that CSR disclosure had significant effect on CFP, but the CSR disclosure had no significant effects on stock price, and CFP had no significant effects on stock prices.Keywords : corporate social responsibility, financial performance, stock price, property sector